Impact of Psychological Distress in Women upon Coping with Breast Cancer: Coping with Breast Cancer - khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2022)
Objective(s): To determine the impact of psychological distress in women upon coping with breast cancer.Methodology: A descriptive design is carried throughout the present study. Convenient sample of (60) woman with breast cancer is recruited from the community. Two instruments, psychological distress scale and coping scale are developed for the study. Internal consistency reliability and content validity are obtained for the study instruments. Data are collect through the application of the study instruments. Data are analyzed through the use of descriptive statistical data analysis approach and inferential statistical data analysis approach.Results: The study findings depict that women with breast cancer have experienced psychological distress and negative coping strategies.Conclusion: The study confirms that psychological distress has an impact upon women’s coping with breast cancer.Recommendations: The study recommends that screening for psychological distress among high-risk breast cancer patients could facilitate timely referral to appropriate psychosocial services.